The Politics of Crime and Criminal Justice - Fairchild, Erika S. (1984)
This volume is about politics, crime, and criminal justice in the United States. As such, it reports on some of the fruits of an increasing amount of research that has been devoted to this topic in recent years. With the exception of one analytical essay on crime as an issue in American politics, all of the articles in the volume are based on original field research